Intra-fraction motion of pelvic oligometastases and feasibility of PTV margin reduction using MRI guided adaptive radiotherapy - Snyder, Jeffrey; Smith, Blake; St-Aubin, Joel; Dunkerley, David; Shepard, Andrew; Caster, Joseph; Hyer, Daniel (Frontiers in Oncology, 2023)
Purpose: This study assesses the impact of intra-fraction motion and PTV margin size on target coverage for patients undergoing radiation treatment of pelvic oligometastases. Dosimetric sparing of the bowel as a function of the PTV margin is also evaluated. Materials and Methods: Seven patients with pelvic oligometastases previously treated on our MR-linac (35 Gy in 5 fractions) were included in this study. Retrospective adaptive plans were created for each fraction on the daily MRI datasets using PTV margins of 5 mm, 3 mm, and 2 mm. Dosimetric constraint violations and GTV coverage were measured as a function of PTV margin size. The impact of intra-fraction motion on GTV coverage was assessed by tracking the GTV position on the cine MR images acquired during treatment delivery and creating an intra-fraction dose distribution for each IMRT beam. The intra-fraction dose was accumulated for each fraction to determine the total dose delivered to the target for each PTV size. Results: All OAR constraints were achieved in 85.7%, 94.3%, and 100.0% of fractions when using 5 mm, 3 mm, and 2 mm PTV margins while scaling to 95% PTV coverage. Compared to plans with a 5 mm PTV margin, there was a 27.4 ± 12.3% (4.0 ± 2.2 Gy) and an 18.5 ± 7.3% (2.7 ± 1.4 Gy) reduction in the bowel D0.5cc dose for 2 mm and 3 mm PTV margins, respectively. The target dose (GTV V35 Gy) was on average 100.0 ± 0.1% (99.6 – 100%), 99.6 ± 1.0% (97.2 – 100%), and 99.0 ± 1.4% (95.0 – 100%), among all fractions for the 5 mm, 3 mm, and 2 mm PTV margins on the adaptive plans when accounting for intra-fraction motion, respectively. Conclusions: A 2 mm PTV margin achieved a minimum of 95% GTV coverage while reducing the dose to the bowel for all patients.